The Impact of Personal Selling, E-Wom and E-Referral Using Brand Image as Mediating Variable on Purchase Intention of Intune Productions - Natalia, Monica; Dewi, Liliana (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
The need for sound and music in advertising is growing every year, especially when Covid-19 accelerates the need for brands to go digital. InTune Productions is a music production company based in Surabaya, Indonesia. Specializing in jingle, sound-logo, and background music, InTune Productions has worked with various companies to increase their brand awareness through sound and music. This research aims to analyze the impact of personal selling, e-WOM and e-referral using brand image as mediating variable on purchase intention of Intune Productions. This research is quantitative research where the data collected from questionnaires will be analyzed statistically using Structural Equation Modelling Partial Least Square in SmartPLS program. Population of this research is 256 members of JCI East Java. The researcher uses purposive sampling and found 98 samples. The result shows that personal selling, e-WOM and e-referral do not have a significant effect towards purchase intention. E-referral also does not have a significant effect towards brand image. However, brand image has a positive significant effect towards purchase intention, as well as acting as a mediating variable between personal selling and e-WOM towards purchase intention.